An SOE estimation model considering electrothermal effect for LiFePO4/C battery. (17th July 2017) - Lin, Shili; Song, Wenji; Lv, Jie; Feng, Ziping; Zhang, Yanhui; Li, Yongliang
Summary: The state of energy (SOE) is an important performance parameter and evaluation index for LiFePO4 /C battery since the available energy can be known more intuitively through SOE compared with state of charge (SOC). First, in order to improve the estimation accuracy of SOE, a novel estimation model combining electrical energy and thermal energy is put forward by studying the effects of discharge rate to the change laws of all kinds of energy inside the battery cell. Moreover, the concepts of unavailable energy E u, maximum allowable energy E, and discharge energy efficiency η are originally proposed based on the analysis of energy consumption. Second, the parameter of actual maximum energy and energy consumption revised by the case of LiFePO4 /C battery can give an example to show the specific steps for improving the estimation accuracy of SOE during any integration time by using the novel SOE estimation model. Lastly, 2 international standard test experiments of EV are conducted to show the correction of SOC can efficiently limit the error below 4.6% and also indicate the novel SOE estimation method suitable for application area.